Analisis Kebijakan Alokasi Anggaran Daerah Terhadap Pelaksanaan Standar Pelayanan Minimal (SPM) Pada Dinas Sosial Provinsi Maluku - Manusiwa, Marisa Friskila; Laurens, Samson; Madubun, Jusuf (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the regional budget allocation policy toward the implementation of Minimum Service Standards (SPM) at the Social Affairs Office of Maluku Province. SPM represents the mandatory indicators that must be achieved by local governments in providing basic services, particularly to vulnerable groups such as the elderly, neglected children, and persons with disabilities. This research employs a descriptive qualitative approach with data collected through interviews, observation, and documentation. The analysis focuses on four main aspects: planning and budget prioritization, allocation and utilization effectiveness, institutional readiness, and monitoring and accountability. The findings indicate that while SPM programs have been aligned with regional planning documents, the integration of basic social needs data remains weak. Budget utilization effectiveness is also suboptimal, as reflected in the gap between targeted outcomes and actual achievements. Furthermore, institutional capacity and human resources are not fully prepared to implement SPM programs, and oversight is mostly administrative with limited public engagement. Therefore, strengthening cross-sectoral coordination, enhancing institutional capacity, and improving participatory monitoring systems are essential to ensure more effective budget allocation. This study recommends evidence-based policymaking as a foundation for social budget decisions.